PENGENDALI PINTU MENGGUNAKAN WEB SERVER DAN RFID BERBASIS WEMOS D1 MINI UNTUK MONITORING PEGAWAI PADA BADAN PUSAT STATISTIK KABUPATEN TANGERANG - fredy susanto; Maimunah Maimunah; Didi Tegar Tiasto (Teknik Informatika, 2018)
To improve the quality of employees in an office there should be a system that monitors the entry of employees during working hours, the main door of a corporate office is made for incoming and outgoing access. Therefore, it takes a device that can solve the problem, then it takes a system that can know when and who comes in and the leader can be able to find out to be the material of study. Finally, the idea came up to make a door controller that is based on Smart Card or RFID (Radio Frequency Identification) that bundling the Mini Wemos D1 microcontroller as the brain of the main Door control in this research. RFID automatically unlocks the door, then Webserver serves as an alternative if RFID Tags are left behind or lost. As a tool implementation tool, RFID is used for identification based on the identity of employees to be able to access and recognize it, so that only registered employees in the database can use this door control system. Wemos D1 mini microcontroller-based door controller system, has 2 functional tasks, including: Auto open-lock door and Monitoring out the entry of employees at the BPS office, Observation research conducted on the main door of BPS office Kab. Tangerang. Thus through the application of this system, the main work function of the main door at BPS Kab. Tangerang has changed to automatic..